The Royal Thai Police’s Use of Force Policy: A Guideline for Reducing Criminal Violence - Chalermyot, Sitthipat (Suan Dusit Graduate School Academic Journal, 2022)
The use of force by police officers had to be enforced according to the Universal Declaration of Human Rights. It is permitted under the use of force policy of United Nations and Thailand is also a member of United Nations. The Royal Thai Police studied and regulated it to be in agreement with the principles of human rights and Thai laws and announced new policy on use of force in 2016. The Royal Thai Police provided better understanding on this matter to police officers before publicizing guidance to communities. The main point of this was to allow police officers to quickly tailor a response and apply force, if necessary. Situational awareness was essential, and officers were trained to judge when a crisis required the use of force to regain control of a situation. The use of force by police officers was considered interdisciplinary and behavior science approach which can answer all operational questions related with Dos’ and Don’ts. This article focused on issues in other countries and issues that were going to take place in Thailand by presenting background and contents on the use of force policy in Thailand before reviewing the use of force policy in other countries that was progressing rapidly. Although Thailand had just begun to adopt this policy because of cultural differences and legal restrictions.